2016
DOI: 10.4238/gmr.15017769
|View full text |Cite
|
Sign up to set email alerts
|

Array-CGH analysis in patients with intellectual disability and/or congenital malformations in Brazil

Abstract: ABSTRACT. In several patients, intellectual disability and/or congenital malformation may be attributed to chromosomal changes. In this study, we conducted an array-CGH test of 200 patients from the Northeast of Brazil with intellectual disability and/or congenital malformation. Blood samples were collected from the proband and from their parents when possible. DNA was extracted and investigated using the array-CGH test. Findings were evaluated for the pathogenicity in databases of benign and pathogenic change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
3
8
0
3
Order By: Relevance
“…In this study, the CMA in 63 individuals with DD/ID revealed pathogenic CNVs in 20 (32%) cases. This diagnostic yield is higher than the yields obtained in earlier studies (Miller et al 2010;Wincent et al 2011;Palmer et al 2014;Vianna et al 2016;Di Gregorio et al 2017). However, the reason for this higher detection rate was the inclusion of 12 individuals with abnormal karyotype results prior to the CMA.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In this study, the CMA in 63 individuals with DD/ID revealed pathogenic CNVs in 20 (32%) cases. This diagnostic yield is higher than the yields obtained in earlier studies (Miller et al 2010;Wincent et al 2011;Palmer et al 2014;Vianna et al 2016;Di Gregorio et al 2017). However, the reason for this higher detection rate was the inclusion of 12 individuals with abnormal karyotype results prior to the CMA.…”
Section: Discussionmentioning
confidence: 58%
“…In South America, very few studies performing CMA in individuals with DD/ID exist (Krepischi-Santos et al 2006;Lay-Son et al 2015;Vianna et al 2016;Zanardo et al 2017). However, none of them compared the clinical features among individuals with or without GIs.…”
Section: Discussionmentioning
confidence: 99%
“…Se destaca en este trabajo el tamaño de la muestra, que sería la más grande reportada en Sudamérica 12,17,18 y que se incluyeron pacientes provenientes de todo Chile, lo que contribuye, con mayor precisión, a conocer la prevalencia de este tipo de alteraciones genéticas en la población chilena. Por otro lado, es importante destacar que la asociación de un diagnóstico positivo por CMA con factores como el sexo del paciente, edad y el tipo de diagnóstico no habían sido descritos antes en población chilena.…”
Section: Discussionunclassified
“…Tanto los TN como las AC se manifiestan en la infancia, lo que amerita su derivación en esta etapa de la vida 1,2 . La tasa de diagnóstico de 19% estimada en el presente estudio podría ser considerada como la prevalencia de estos desbalances en población chilena con TN, AC o ambos, lo que concuerda además con las cifras promedio reportadas internacionalmente (entre 15 a 20%) 11,17,18 . Sin embargo, esta podría ser mayor, ya que en el estudio previo realizado en Chile 12 se detectó variantes clínicamente significativas en 25% de los pacientes, porcentaje que sube a cerca de 29%, si se consideran solo aquellos pacientes con cariotipo convencional normal.…”
Section: Discussionunclassified
“…Благодарение на високата си резолюция и чувствителност, микрочиповата технология се превърна в ключов подход при диагностицирането на пациенти с множество вродени малформации, и/ или умствено увреждане [21].…”
Section: дискусияunclassified